Writers' & artists' yearbook 2016 : the essential guide to the media and publishing industries : the perfect companion for writers of fiction and non-fiction, poets, playwrights, journalists, and commercial artists.: the essential guide to the media and publishing industries : the perfect companion for writers of fiction and non-fiction, poets, playwrights, journalists, and commercial artists. (2015 copyright 2015) - Unknown
No abstract available